The Raw pH in Plants: A Multifaceted Parameter - Masoero, Giorgio; Cugnetto, Alberto (Journal of Agronomy Research, 2018)
The measurement of the in vivo raw pH of vegetative organs is a unusual way obtaining plant knowledge. The authenticity of the pH parameter of the leaf and its independence from soil pH has already been highlighted. In the present work we observe how and to what extent water-temperature mechanisms as well as bio-fertilizers inocula can affect the raw pH and how great the biodiversity is in plants. A trial with Arabidopsis thaliana in a phytotrone has shown that, in the dark, the raw pH did not change from +18 to +35 °C (b = -0.0027 N.S.), while in the light, the regression coefficients were significant and negative, and the acidification in the leaves progressed from high (-0.0097) to normal (-0.0127) and then to low (-0.0370) water level. We have confirmed that warming induces a decrease of raw petiole pH of -0.070 pH C°-1 in grapevine leaves. In accordance with water-temperature mechanisms, the raw pH in grapevines has been found to be significantly higher in well-watered plants (pH = 4.29) than in stressed ones (4.12), with a pH decay of -3.9%. On the other hand, an average reduction of 0.10 units of raw pH would signal an increase in water stress of about -0.59 Mpa. Among the phenomena that can influence the raw pH, we have outlined three biotic factors: i) acidification as a result of a symbiotic farming fertilization i.e through the use of mycorrhizal and microbial fertilizers, with an average decay of around -3%, as a probable signature of symbiosis; ii) an “acida plantarum natura” scenario over 49 species, ranging from pH 3.06 to 6.38 ; iii) a strong (R2= 0.9) inverse polynomial pseudo-relationship of the number of fungicide sprays on the raw pH in a set of 15 species. It is suggested that this simple new multifaceted parameter can deserve interest.
Keywords: Plant pH; Aerial Temperature; Water Stress; Arabidopsis Thaliana; Biofertilizers; Mycorrhiza